(untitled) (REVISTA NODO, 2025)
Radio stimulates the listening and promotes the imagination. It informs, entertains and accompanies daily life with content sent through the electromagnetic spectrum and received through decoding devices. Its popularization as mass media began in 1920, when Leon Theremin gave electronic sounds to music with his etherphone, a musical instrument born from radio operation that required no touch to play it. 105 years later, it still amazes the audience. The variation of the monophonic sound is achieved by the distant interaction between the human body and both the electrical and magnetic forces emanating from its antennas, making a subtle connection with the device circuit, perceivable inside and outside of the body. An aesthetic experience beyond mere listening and that modifies the utilitarian relationship with these artifacts. To corroborate this, the attendees of the experimental laboratory Theremin and Radio Art, held in Manizales (Colombia) during March 2024, share their perceptions, expressive connections and flows of meaning.